The Effect Of Using Qris On BSI Mobile Banking On MSMES Customer Satisfaction In Medan - Atha, Muhammad Alwan; Lubis, Fauzi Arif; Rahmani, Nur Ahmadi Bi (UNIVERSITAS PAKUAN, 2024)
The purpose of this study was to determine the effect of using QRIS in the BSI Mobile Banking Application on MSME customer satisfaction in Medan, this research was conducted at MSMEs in Medan. The type of research used is quantitative research. Sampling using saturated sampling technique, because researchers only took a sample of MSME respondents totaling 42 respondents. The data collection technique uses a questionnaire that has been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple regression, classical assumption test, t test, f test, coefficient of determination. The results of the research conducted show that the coefficient of determination (adjusted R square) is 0.564 or 56.4%. That the use of QRIS in the BSI Mobile Banking Application partially affects MSME Customer Satisfaction in Medan.